Skin Detachment and Regrowth in Toxic Epidermal Necrolysis - Laurence Feldmeyer; Thomas Harr; Antonio Cozzio; Lars.E. French; Alexander A. Navarini (Karger Publishers, 2010)
Toxic epidermal necrolysis is a rare but clinically well-described dermatological pathology. However, clinical pictures of this disorder in text books do not reflect its dynamic evolution. Usually, the desquamative post-bullous stage is represented, neglecting the initial bullous stage as well as the skin healing. With one clinical case, we provide a day-after-day illustration of the evolution of a patient suffering from toxic epidermal necrolysis. During one month, a skin area of a limb was regularly photo-documented.